2005
DOI: 10.1002/dmrr.591
|View full text |Cite
|
Sign up to set email alerts
|

Do adiponectin, TNFα, leptin and CRP relate to insulin resistance in pregnancy? Studies in women with and without gestational diabetes, during and after pregnancy

Abstract: Background The role of adiponectin, tumour necrosis factor α (TNFα), leptin and C-reactive protein in the insulin resistance of pregnancy is not clear. We measured their levels in women with gestational diabetes (GDM) and in controls, during and after pregnancy, and related them to insulin secretion and action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
122
1
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(155 citation statements)
references
References 46 publications
(67 reference statements)
15
122
1
6
Order By: Relevance
“…However, these correlations were lost in the pregnant subjects; in accordance to our study, McLachlan et al (25) found no correlation between adiponectin and insulin sensitivity, as estimated by intravenous glucose tolerance test (IVGTT), in 19 older Australian pregnant women with higher BMI; on the other hand, in contrast to our study, in 219 Asian pregnant women of similar BMI, adiponectin was negatively correlated to insulin and indirect IR parameters during oral GTT (26). Differences in sample size, race, or methodology could be responsible for this discrepancy.…”
Section: Discussionsupporting
confidence: 92%
“…However, these correlations were lost in the pregnant subjects; in accordance to our study, McLachlan et al (25) found no correlation between adiponectin and insulin sensitivity, as estimated by intravenous glucose tolerance test (IVGTT), in 19 older Australian pregnant women with higher BMI; on the other hand, in contrast to our study, in 219 Asian pregnant women of similar BMI, adiponectin was negatively correlated to insulin and indirect IR parameters during oral GTT (26). Differences in sample size, race, or methodology could be responsible for this discrepancy.…”
Section: Discussionsupporting
confidence: 92%
“…This observation is consistent with studies showing an increase in plasma TNF-in late pregnancy (Kirwan et al, 2002;Clapp & Kiess, 2000;Boyd et al, 2007). TNF-correlates inversely with insulin secretion in normal pregnancy and was significantly higher in GDM group (McLachlan et al, 2006). TNF-alpha mRNA and protein are present in human placenta and uterine cells at both early and late stages of gestation (Chen et al, 1991).…”
Section: Tumor Necrosis Factor-α (Tnf-α)supporting
confidence: 88%
“…Recently, it was shown that serum hsCRP decreased while TNFalpha and adiponectin levels remained unchanged four months postpartum in pregnancies with and without GDM. 39 On the other hand, other investigators found hypoadiponectinemia during the 3 rd and 4 th day postpartum in normal lactating women. 40,18 It has been suggested that this hypoadiponectinemia might be due to the suppression of adipocyte-produced adiponectin by prolactin.…”
Section: Discussionmentioning
confidence: 94%